ASSOCIATION BETWEEN COGNITIVE IMPAIRMENT AND 6-12 MONTHS QUALITY OF LIFE IN ISCHEMIC STROKE - Kadex Reisya Sita Damayanti; Pinzon, Rizaldy Taslim (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Stroke is a major contributor to deaths and disabilities worldwide. Impaired cognitive function is often found in ischemic stroke patients. Disability due to stroke causes functional impairment in various quality of life domains. Cognitive function is one of the predictors of the quality of life. There are still not many studies on cognitive impairment and quality of life in ischaemic stroke patients in Indonesia. Objective: To compare the average quality of life of 6-12 months of stroke patients at the Bethesda Hospital Yogyakarta Neurology Center based on the presence of cognitive impairment Methods: The study used a retrospective cohort study design. Subject data were obtained from the Bethesda Hospital Yogyakarta stroke registry. All risk factor data (laboratory and clinical) and medication were obtained during admission. Cognitive impairment was measured using the Mini Mental State Examination (MMSE) and Clock Drawing Test (CDT). The questionnaire used was World Health Organization Quality Of Life BREF (WHOQOL-BREF). Results: From 113 patients, average quality of life of patients in domain 1, domain 2, and domain 3 was not significant (p > 0.05). A significant mean difference between cognitive impairment and quality of life was found in domain 4 (p = 0.025). Analysis of the confounding variables showed that a history of hypertension, National Institute of Health Stroke Scale (NIHSS) score, diabetes, and atrial fibrillation also had an effect on the patient's quality of life. Conclusion: Cognitive impairment does not have a significant effect on quality of life, especially in the domains of physical health, psychological health, and social relations, but has a significant effect on the environmental health domain of ischemic stroke patients.